A structure-specific small molecule inhibits a miRNA-200 family member precursor and reverses a type 2 diabetes phenotype. Issue 2 (17th February 2022) - Haniff, Hafeez S.; Liu, Xiaohui; Tong, Yuquan; Meyer, Samantha M.; Knerr, Laurent; Lemurell, Malin; Abegg, Daniel; Aikawa, Haruo; Adibekian, Alexander; Disney, Matthew D.
Summary: MicroRNA families are ubiquitous in the human transcriptome, yet targeting of individual members is challenging because of sequence homology. Many secondary structures of the precursors to these miRNAs (pri- and pre-miRNAs), however, are quite different. Here, we demonstrate both in vitro and in cellulis that design of structure-specific small molecules can inhibit a particular miRNA family member to modulate a disease pathway. The miR-200 family consists of five miRNAs, miR-200a, -200b, -200c, -141, and -429, and is associated with type 2 diabetes (T2D). We designed a small molecule that potently and selectively targets pre-miR-200c's structure and reverses a pro-apoptotic effect in a pancreatic β cell model. In contrast, an oligonucleotide targeting the RNA's sequence inhibited all family members. Global proteomics and RNA sequencing analyses further demonstrate selectivity for miR-200c. Collectively, these studies establish that miR-200c plays an important role in T2D, and small molecules targeting RNA structure can be an important complement to oligonucleotides. Graphical abstract: Highlights: A small molecule can selectively target an individual microRNA in a cluster Selective base pair binders enhance the affinity of RNA structure-targeting molecules Inhibition of miR-200c represses pancreatic β cell apoptosis observed in T2D Abstract : microRNA (miR)-200c, part of a microRNA family with significant sequence homology, is associated with type 2 diabetes (T2D). This sequence homology makes selective inhibition of miR-200c difficult. Haniff and Liu et al. exploit structural differences to inhibit miR- 200c's biogenesis selectively with a small molecule, defining its pathway in T2D.